DEVELOPING MICRO, SMALL AND MEDIUM ENTERPRISES THROUGH ENTREPRENEURSHIP TRAINING AND GROWING ENTREPRENEURSHIP MOTIVATION (EMPIRICAL CASE STUDY OF SMALL AND MEDIUM ENTERPRISES IN EAST JAKARTA SMALL INDUSTRIES VILLAGE) - Siska Yuli Anita (Dinasti Publisher, 2020)
This study aims to analyze: 1) The effect of entrepreneurship training on the motivation of micro and small business entrepreneurs in the East Jakarta Small Industrial Area. 2) The effect of entrepreneurship training on the development of micro small and medium enterprises in the East Jakarta Small Industrial Village area 3) The influence of motivation on the development of micro small and medium businesses in the East Jakarta Small Industrial Village area. This research uses a quantitative method using SEM Lisrel 8.8 Program analysis tools. The number of respondents was 253 respondents of micro small and medium enterprises in the East Jakarta Small Industrial Village. The results of the study stated: 1) the influence of entrepreneurship training on the motivation of micro and small business entrepreneurs in the region East Jakarta Small Industrial Village. 2) the influence of entrepreneurship training on the development of micro small and medium enterprises in the East Jakarta Small Industrial Area 3) The influence of motivation on the development of micro small and medium businesses in the East Jakarta Small Industrial Village area.